Age Estimation Based on Third Molar Classification: Modification of The Demirjian Method - ., Firdaus; Wisnu, Fredy Rendra Taursia; Afdilla, Nurul (FKG Universitas Syiah Kuala, 2025)
Age estimation is an important factor in identifying a person, especially in forensic dentistry. One of the methods used in determining age estimation is based on the classification of third molar using the modified Demirjian method. This method can be performed on individuals who already undergoing the growth and development process of the third molars. The purpose of this research was to determine age estimation based on the classification of third molars at the Regional General Hospital of Rokan Hulu, Riau Province. This descriptive observational study involved 63 samples of ethnic Malay based on panoramic photos in medical records from June 2020 to August 2023. The results of this study showed that among males, 23 sample (92%) had a difference of less than one year between chronological age and estimated age. Among females, 28 samples (74%) had a difference of less than one year between chronological age and estimated age. It can be concluded that the estimated age closely approximates the chronological age in both males and females in Rokan Hulu Regency.